Computer Science Education in the 21st Century. - Patterson, David A. (Communications of the ACM, 2006)
This article presents a letter from ACM president David A. Patterson. Patterson offers four concrete suggestions for how to draw students to computer science (CS). Patterson's goal is the creation of a CS curriculum that reflect current opportunities and challenges in information technology rather than those of the 1970s. Patterson expressed concern that although many professors use programming languages like Java, few have embraced modern programming environments like the Eclipse development platform and the JUnit testing framework.